Circulating progenitor cell response to exercise in wheelchair racing athletes - Niemiro, G. M.; Edwards, T.; Barfield, J. P.; Beals, J. W.; Broad, E. M.; Motl, R. W.; Burd, N. A.; Pilutti, L. A.; De Lisio, M. (Medicine & Science in Sports & Exercise, 2018)
INTRODUCTION: Circulating progenitor cells (CPC) are a heterogeneous population of stem/progenitor cells in peripheral blood that participate in tissue repair. CPC mobilization has been well characterized in able-bodied persons but has not been previously investigated in wheelchair racing athletes. The purpose of this study was to characterize CPC and CPC subpopulation mobilization in elite wheelchair racing athletes in response to acute, upper-extremity aerobic exercise to determine whether CPC responses are similar to ambulatory populations.